Museum, archaeology and nation: González Suárez and the Sociedad de Estudios Histórico-Americanos in early twentieth-century Ecuador. Issue 1 (2nd January 2019) - Bedoya Hidalgo, María Elena
ABSTRACT: This article proposes an analytical reading of the ways in which an Ecuadorian museology was conceived at the beginning of the twentieth century. The Ecuadorian state, unlike other countries in the region, showed little interest in promoting and sponsoring the establishment of academies or institutes for the research of history in specialised circuits that were linked with ideas of the public museum. The construction of a national museum of archaeology was a process that began in the nineteenth century and involved a specialised scientific sociability that sustained this process as history, anthropology and archaeology were in development as sciences in those years. People such as Federico González Suárez and a Catholic conservative elite participated in this process during the first decades of the twentieth century.